Passive immunization with influenza haemagglutinin specific monoclonal antibodies - Rudraraju, Rajeev (Hum Vaccin Immunother, 2018)
The isolation of broadly neutralising antibodies against the influenza haemagglutinin has spurred investigation into their clinical potential, and has led to advances in influenza virus biology and universal influenza vaccine development. Studies in animal models have been invaluable for demonstrating the prophylactic and therapeutic efficacy of broadly neutralising antibodies, for comparisons with antiviral drugs used as the standard of care, and for defining their mechanism of action and potential role in providing protection from airborne infection.